38‐1: Invited Paper: Ink‐Jet‐Printed OLEDs for Display Applications. Issue 1 (May 2016) - Levermore, Peter; Schenk, Thorsten; Tseng, Hsin‐Rong; Wang, Hsing‐Ju; Heil, Holger; Jatsch, Anja; Buchholz, Herwig; Böhm, Edgar
Abstract : We report performance of red, green and blue inkjet printed organic light emitting diodes with common blue device architecture. Device efficiency, voltage, color and lifetime are reported, and emission profile discussed. We demonstrate that inkjet printed OLED performance metrics are rapidly approaching commercial requirements for display applications, and discuss strong potential for further progress.